Generational Model of Warfare and Evolution of Hybrid Warfare: A Review of Diverse Perspectives - Muhammad Waqas Haider; Tahir Mahmood Azad, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
This paper aims to explain the generational model of warfare and to elaborate theory of Hybrid Warfare. The paper endeavours to clarify the conceptual understanding of Hybrid Warfare by evaluating the perspectives from different parts of the world. The dynamics of war have changed with the passage of time and the war in contemporary times has taken a different form where conventional and irregular forces are visible on the same battlefronts. The international strategic landscape has transformed in the aftermath of the cold war as the emerging actors and strategies cannot be placed under the existing categories because they do not follow the existing models of warfare. The defence analysts and academics theorise the emergence of a different and innovative type of warfare called Hybrid warfare. Hybrid Warfare has diverse and multifaceted perspectives around the world. A comprehensive understanding of the generational model of warfare and conceptual clarity about our understanding of the changing nature of warfare is a prerequisite to counter contemporary challenges.